Strategic Communications and Corporate Branding: a Study of Jebsen & Jessen Indonesia Group - Heny Wahyu Tamara Dwi Lestari; Dindin Dimyati; Mohammad Shihab (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2017)
Corporate communications hold a vital function to maintain the company’s positive image and reputation in front of stakeholders. A corporate communications practitioner must be able to handle a variety of communication processes in an organization, including to determine the right strategy to reach its communications goal. The purpose of this research is to analyze the corporate communications strategy of Jebsen & Jessen Indonesia Group to create its corporate branding and reflect it with public relations strategic planning process. The researcher gathered the primary data from in-depth interview with key informant and combine it with secondary data from other relevant data. Afterwards, it was verified by triangulation to strengthen the credibility of data and continue with analysis process. This research concluded that Jebsen & Jessen Indonesia Group has implemented its corporate branding strategy accordingly to public relations strategic planning process. Some of the targets have been achieved in one year period, however there have been suggestions to improve the future corporate branding strategy formation.